Vessel traffic scheduling method for the controlled waterways in the upper Yangtze River. (15th January 2019) - Liang, Shan; Yang, Xiaoyue; Bi, Fangquan; Ye, Chengyang
Abstract: An Inland Waterway Transportation System is often claimed to be safe, efficient and economic. However, traffic congestion and vessel collision have become serious threats to marine safety, especially in the one-way waterways. The aim of this paper is to rank the vessels in the controlled waterways of the upper Yangtze River and to generate the optimal traffic commands for each vessel so as to ensure marine safety and traffic efficiency. In this study, the proposed approach is based on the combination of Fuzzy Analytical Hierarchy Process (FAHP) with an Expert System (ES). Vessel data collected from Automatic Identification Systems (AIS) are first analyzed by experts, and some external environment and internal factors are selected as Significant Influencing Factors (SIFs). FAHP is then used for modelling a hierarchical structure and determining the weight of each SIF. Finally, the sorted vessel sequence and appropriate traffic commands can be achieved using ES. The experiment result shows that the waiting time of vessels is averagely decreased about 22 min compared with the existing Traffic Signal Revealing System. This will not only significantly improve the efficiency and accuracy of the vessel traffic scheduling, but also increase the waterway capacity by reducing the travelling time. Highlights: A novel approach is proposed to enhance vessel traffic scheduling for the controlled waterways in the upper Yangtze River. Based on Fuzzy Analytical Hierarchy Process and the Expert System, the AIS data are discussed and analyzed in detail. Traffic congestion and vessel collisions in the controlled waterways could be preventable using the proposed approach. The reliability and efficiency of proposed method have been verified by comparing with Traffic Signal Revealing System.